Pengaruh Residu Karbofuran terhadap Penyakit Hawar Upih Daun Rhizoctonia solani pada Padi - Christanti Sumardiyono (Universitas Gadjah Mada, 1997)
The purpose of this study was to know the side effect of carbofuran on sheath blight disease on rice caused by Rhizoctonia solani. The results showed that carbofuran residue which was maybe its metabolite decrease disease intensity of sheath blight. The carbofuran residue was detected on rice stem two months after treatment at the dose of 8.5, 17.0, and 34.0 kg/ha, while in the soil treated at 34.0 kg/ha it was not detected.